2006
DOI: 10.3758/bf03193727
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric differences for the integration of stimulus levels and their contents: Evidence from bilateral presentations

Abstract: Several studies have demonstrated that hemispheric differences for the processing of hierarchical letter stimuli are more likely to occur when the letters at the levels are associated with conflicting responses. Typically, a single stimulus is presented, so that the conflict occurs between the global and the local levels of the same stimulus. Our hypothesis is that in this situation, conflict resolution requires integration of the letters and their respective levels and that the hemispheres differ in this inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…These mechanisms probably rely on temporal-parietal areas and play a supervisory role in the attentional control for global/local processing within the prestriate cortex (Yamaguchi et al, 2000). For example, the classical hemispheric asymmetries for global/local processing are more robust in divided- than focused-attention tasks (Van Kleeck, 1989; Heinze et al, 1998; Yovel et al, 2001), and when solving information conflict between levels is necessary (Hübner and Malinowski, 2002; Malinowski et al, 2002; Volberg and Hubner, 2004, 2006; Hübner and Volberg, 2005; Hübner et al, 2007). Additionally, hemispheric asymmetries due to the global-local distinction can be obscured by some aspects of the material which may produce co-varying effects due to the involvement of other processes which are also lateralised.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms probably rely on temporal-parietal areas and play a supervisory role in the attentional control for global/local processing within the prestriate cortex (Yamaguchi et al, 2000). For example, the classical hemispheric asymmetries for global/local processing are more robust in divided- than focused-attention tasks (Van Kleeck, 1989; Heinze et al, 1998; Yovel et al, 2001), and when solving information conflict between levels is necessary (Hübner and Malinowski, 2002; Malinowski et al, 2002; Volberg and Hubner, 2004, 2006; Hübner and Volberg, 2005; Hübner et al, 2007). Additionally, hemispheric asymmetries due to the global-local distinction can be obscured by some aspects of the material which may produce co-varying effects due to the involvement of other processes which are also lateralised.…”
Section: Discussionmentioning
confidence: 99%
“…Accounts proposed so far for explaining this difference (Heinze et al, 1998;Yovel et al, 2001) are rather restricted and, therefore, cannot explain our additional results. For instance, in various studies from our group (Hübner, 1997(Hübner, , 1998Hübner & Volberg, 2005;Malinowski et al, 2002;Volberg & Hübner, 2004, 2006, we have demonstrated that VFEs also occur reliably with selective-attention tasks, but only for incongruent stimuli-that is, when global and local information activate competing responses-and mainly when the target level is randomized. This pattern cannot be explained by the current accounts.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they cannot explain why response conflict supports the appearance of VFEs in selective-attention tasks Hübner & Volberg, 2005;Van Kleeck, 1989;Volberg & Hübner, 2004, 2006. Therefore, it would be desirable to have a more general theory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that HIV-1-related impairment in attentional control would be related to compromised integrity in anterior and middle callosal fibers connecting frontal and parietal cortices. Attentional control is required when local and global information is incongruent (i.e., a global E made up from local Ts) (Hibi, Takeda, & Yagi, 2002; Müller-Oehring et al, 2007; Navon, 1977; Proverbio, Minniti, & Zani, 1998) and is associated with conflicting responses (Müller-Oehring et al, 2007; Volberg & Hübner, 2006). Because we had observed earlier (Müller-Oehring et al, 2007, 2009) that redundant target information at both local and global processing levels results in response facilitation, an effect attributable to perceptual preattentive processing (Martin, Sorensen, Robertson, Edelstein, & Chirurgi, 1992, Martin et al, 1995; Sorensen, Martin, & Robertson, 1994; Tzelgov, Henik, & Berger, 1992), we assumed that HIV-1-related impairment in local-global facilitation would be related to compromise in posterior callosal microstructural integrity connecting occipito-temporal visual processing areas.…”
Section: Introductionmentioning
confidence: 99%